Neem (Azadirachta indica) in Context of Intellectual Property Rights (IPR) - Ahmad1, Ompal Singh1*, Zakia Khanam2; Jamal (Recent Research in Science and Technology, 2011)
India has come alive to the need for recognition and protection of intellectual property. In post GATT regime, India has transformed from purely agricultural to agricultural-cum-industrially developed nation. The Industrial progress of a country generally depends upon inventive talents of the entrepreneurs and the number of invention made by them. There is a no doubt that India became member to the Uruguay Round of Multilateral Trade Negotiations and also agreement of Trade Related Aspects of Intellectual Property Rights (TRIPS) is a part of the agreements establishing WTO from GATT and India ratified such agreements. This research article express importance of Intellectual Property Rights with special reference to neem products have been patented and some controversial patents on neem.